PENGEMBANGAN SIKAP PROFESIONAL MAHASISWA PENDIDIKAN MATEMATIKA SEBAGAI CALON PENDIDIK - Nurannisa Ridwan; Mawaddah Warahma; Nurul Humairah; Uspiani; Takdirmin (STKIP Subang, 2026)
Professional attitude is an essential competence that must be possessed by prospective teachers, including students of Mathematics Education programs. Teacher professionalism is not only determined by mastery of subject matter and pedagogical skills, but also by professional attitudes reflected in responsibility, discipline, ethics, and commitment to continuous self-development. This article aims to examine the development of professional attitudes of Mathematics Education students as future educators. The method used is a literature review by analyzing various relevant sources such as books, scientific journals, and educational regulations. The results of the study indicate that the development of professional attitudes can be carried out through learning processes in higher education, teaching practice experiences, habituation of professional ethics values, and continuous self-reflection. With well-developed professional attitudes, Mathematics Education students are expected to become competent, responsible, and integrity-driven teachers in the future.